Clean technologies in metallurgic processes trhouhg the design of industrial tanks - Puente Santibáñez, Luis (2007)
Mining and metallurgical activity produces liquid effluents as a waste during the extraction process, which must be treated in order to be disposed in the environment, following governmental and environmental legislation. Big and medium size mining industry carry on environmental projects as it is the trend worldwide, but small size and informal mining did not have between its priorities the environmental issue due to the lack of research on clean technologies related to this sector which finally could influence in make more efficient its processes. The main aim of the research is centered on propose solutions with an experimental basis for design and dimension of containers in processes with chemical precipitation and cementing of dissolved metals in liquid effluents. Laboratory tests are detailed for cementing copper from liquid effluents by means of light scrap iron which allows recover cement of copper with ferrous impurities and strongly reduce the dissolved copper, diminishing the metallic content in the effluent. Flow processes are simulated in order to obtain variables of response like the time of residence in order to deduce the recommended volume of the container. The copper fraction converted from the precipitated copper is around 90% that is an acceptable result, notwithstanding it is recommended apply an adsorption process after the process in order to reach the maximum limits in order to be discharged to the environment.